2010
DOI: 10.1016/j.ydbio.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Alx3-deficient mice exhibit folic acid-resistant craniofacial midline and neural tube closure defects

Abstract: Neural tube closure defects are among the most frequent congenital malformations in humans. Supplemental maternal intake of folic acid before and during pregnancy reduces their incidence significantly, but the mechanism underlying this preventive effect is unknown. As a number of genes that cause neural tube closure defects encode transcriptional regulators in mice, one possibility is that folic acid could induce the expression of transcription factors to compensate for the primary genetic defect. We report th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 64 publications
4
49
0
Order By: Relevance
“…Statistical analysis indicated that differences between wild-type and Alx3-deficient islets are significant (p<0.01; Mann-Whitney U test). Alx3 deficiency in the cranial mesenchyme of developing embryos [35], a major site of Alx3 expression during development [18]. The smaller size observed in Alx3-deficient pancreatic islets may be related to their relatively high proportion of apoptotic cells, and may contribute to impaired islet cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis indicated that differences between wild-type and Alx3-deficient islets are significant (p<0.01; Mann-Whitney U test). Alx3 deficiency in the cranial mesenchyme of developing embryos [35], a major site of Alx3 expression during development [18]. The smaller size observed in Alx3-deficient pancreatic islets may be related to their relatively high proportion of apoptotic cells, and may contribute to impaired islet cell function.…”
Section: Discussionmentioning
confidence: 99%
“…4A,C). Interestingly, expression of the Alx3-related folate-independent transcription factor Alx4 (Lakhwani et al, 2010) was unchanged in LRP2-deficient embryos (Fig. 4B,C).…”
Section: Expression Of the Folate-dependent Gene Alx3 Is Reduced In Lmentioning
confidence: 96%
“…Recently, it was shown that expression of the gene Alx3 (aristaless-family homeobox transcription factor 3) is specifically dependent on folate, and that ALX3 is important for neural tube closure (Kessaris et al, 2006;Lakhwani et al, 2010).…”
Section: Expression Of the Folate-dependent Gene Alx3 Is Reduced In Lmentioning
confidence: 99%
“…23 Although Alx3-deficient mice were originally found to develop with apparent normality, 24 recent studies demonstrated that a significant proportion of them exhibit neural tube closure defects and alterations in craniofacial midline development. 17 Frontonasal dysplasia, a related type of developmental alteration, has been found in humans bearing mutations in the ALX3 gene. 25 In addition, we have observed that about 15% of viable Alx3-null mice exhibit preaxial polydactyly (Fig.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…14 Overlapping functions among different members of this family are likely. [15][16][17] Therefore, it is possible that a defect in one of them may be compensated by the others, resulting in a relatively mild phenotype. In this regard, at least two other aristaless-related proteins have been associated directly or indirectly with pancreatic islet function.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%